Role of computed tomography in sarcopenia detection - E. V. Sheberova; N. K. Silanteva; T. A. Agababian; A. L. Potapov; A. A. Nevolskikh; S. A. Ivanov; A. D. Kaprin (Сибирский онкологический журнал, 2023)
The study aimed to summarize the available data on the role of computed tomography in sarcopenia detection in cancer patients. Material and Methods. A literature search was conducted in the Medline, Scopus, Pubmed, and Elibrary systems. More than 100 articles published in 2008-2022 were analyzed. We included 45 articles in this review. Results. According to the European Consensus, sarcopenia is a syndrome characterized by progressive and generalized loss of skeletal muscle mass and strength due to age-related, neurohumoral changes, malnutrition or muscle catabolism. It is difficult to overestimate the importance of sarcopenia, since this syndrome is one of the five main risk factors for morbidity and mortality in people over 65 years of age. Sarcopenia is mainly observed in inflammatory diseases, malignancy or organ failure. According to most researchers, CT is considered the gold standard method to assess muscle mass and quality. It is a reliable method for quantitative analysis, which was shown in a study based on the comparison of quantitative assessment of various muscle groups based on CT with muscle volume measured on cadaveric tissues. The purpose of this literature review was to highlight the importance of computed tomography for the detection of sarcopenia in clinical practice. Based on the results of the literature analysis, sarcopenia is still a challenge for modern oncology. Sarcopenia negatively affects the prognosis of the disease and quality of life of cancer patients. Sarcopenia may develop due to metabolic changes caused by cancer treatment, as a result of which the degradation of muscle protein begins to prevail over its synthesis. Conclusion. Given the high prevalence and prognostic significance of sarcopenia in oncology, the need for its early diagnosis and active treatment becomes obvious. The use of routine CT examinations for the diagnosis of sarcopenia will allow us to search for possible causes and optimize treatment, determine the likelihood of risks and determine the treatment strategy at an early stage, when therapy can be most effective.